Does the Apolipoprotein E Genotype Increased the Risk of Postoperative Delirium in Adult Patients? - Kiprijanovska, Biljana; Georgieva, Daniela; Kuzmanovska, Biljana; Nancheva, Jasminka; Toleska, Marija; Panov, Sasho (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2023)
Background: The relationship between genetic predisposition and the development of postoperative delirium has not yet been established. The e4 allele of the apolipoprotein E gene has been reported as a genetic risk factor for delirium. Objective: This paper analyzed the relationship between the frequency of genotypes of the APOE rs7412/rs429358 polymorphism, which contains the minor allele e4, and the occurrence of postoperative delirium. Material and Methods: The study included patients aged 65 years and older without pre-existing cognitive impairment admitted to the University Clinic for Traumatology and Orthopedics for operative treatment of a fracture of the upper end of the thighbone. The Confusion Assessment Method (CAM) confirmed the delirium diagnosis. APOE rs7412/rs429358 polymorphism genotypes were determined by molecular genetic analysis using the quantitative real-time amplification method (qRT-PCR) on DNA samples extracted from venous blood leukocytes. Results: The presented results are from analyzed samples and data from 51 patients. Out of these, postoperative delirium was diagnosed in 12 patients, while in 39 patients weren’t registered, and they are the control group in the trial. Conclusion: This study results indicate the association of the studied polymorphism in the apolipoprotein E gene, which contains the minor allele e4, with the occurrence of postoperative delirium in this group of adult patients. A larger group is necessary to reach more valid conclusions.
Keywords: adult patients; apolipoprotein E; genotype; postoperative delirium